Deixis Types Found in Barack Obama’s Speech Text At A Congress Community Muslim American Event in The Mosque In Balthimore - Tiara Widyaiswara; Risa Arismawati (EDULIA: English Education, Linguistic and Art Journal, 2021)
The aim of this research is What are the function and references of the types of deixis found in Barack Obama’s speech text at a congress community Muslim American event in the mosques in Baltimore? The method used in this research is library research qualitative approach. The data source in this research is text of Barack Obama’s speech. The method of collecting data is using documentation. The data were analyses by using Levinson theory. The result of the research are is there are three types of deixis meanly, person deixis has function, place deixis and time deixis. The conclusion of this research in speech text of Barack Obama at a Congress Community Muslim American event in the Mosque in Baltimore some the person deixis has function plural singular and plural pronoun, it singular refers to Barack Obama (as speaker) plural refers to audience. The place deixis has function proximal and distal term, it proximal refers to Mosque in Baltimore where place speaker delivers speech, it distal refers to Community of American Muslims in Africa The time deixis has function proximal and distal term, it proximal refers to Thursday, the day when speaker congress event, it distal refers to the past condition when a act of terrorism. Keywords: Analysis, deixis types, Barack Obama’s speech